Effect of biostimulants on mustard microgreens grown under different cultivation conditions - Clément, Justine; Delisle-Houde, Maxime; Nguyen, Thi; Dorais, Martine; Tweddell, Russell (Phytoprotection, 2024)
Ten products, commercially available as biostimulants or reported for their biostimulating properties, were tested under conventional and organic growing systems for their effects on mustard microgreens (Brassica juncea) grown in presence of abiotic (salt) or biotic (Pythium ultimum) stress. Drench application of wollastonite (calcium silicate) significantly improved the germination rate of mustard seeds sown in a substrate inoculated with P. ultimum in conventional growing system exclusively. In both growing systems, no significant effect of biostimulants was observed on the dry biomass or the proportion of healthy microgreens grown in presence of P. ultimum. None of the biostimulants significantly increased the germination rate of seeds exposed to a salinity stress in both growing systems while humic acid, triacontanol, chitosan, and Bacillus subtilis PTB185 significantly decreased the germination rate of seeds exposed to 40, 80 or 120 mM NaCl L-1 under conventional or organic management. Seed treatment with Trichoderma harzianum T-22 and humic acid resulted in microgreens with a significantly higher dry biomass when subjected to 40 and 80 mM NaCl L-1 under conventional and organic management, respectively. The study showed that the effects of the biostimulants vary from beneficial to detrimental and that plant response to biostimulants is influenced by the cultivation conditions.